1970
DOI: 10.1111/j.1096-3642.1970.tb00735.x
|View full text |Cite
|
Sign up to set email alerts
|

Observations on Australian Glaucidae (Mollusca: Opisthobranchia)

Abstract: Glaucilla Bergh, 1868 is positively recorded for the first time from eastern Australia, together with Glaucur Forster, 1777. The former is allocated to G. mrginuta Bergh, 1868 and the latter to G. atlanticuc Forster, 1777. Glaucilla has multiseriate ceratal clusters (uniseriate in Glaucus), an unarmed penis (armed with a chitinous spine in Glaucas) and several anatomical peculiarities. Glaucid nudibranchs feed upon species of Velella, Physalia and Porpita; nematocysts of Physalia are subsequently employed for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

1974
1974
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 4 publications
1
8
0
1
Order By: Relevance
“…Unlike many pelagic taxa [3,6], for which morphological data are unavailable, aeolid nudibranch morphology (including Glaucus spp.) has been studied in detail [10,[21][22][23][24][25][26][27]. To test for anatomical corroboration that these four G. marginatus mt molecular clades represent cryptic morphospecies, we identified three anatomical areas most likely to differ in cases of recent speciation: external morphology, the chitinous feeding structures (radulae and jaws) and the reproductive system.…”
Section: Resultsmentioning
confidence: 99%
“…Unlike many pelagic taxa [3,6], for which morphological data are unavailable, aeolid nudibranch morphology (including Glaucus spp.) has been studied in detail [10,[21][22][23][24][25][26][27]. To test for anatomical corroboration that these four G. marginatus mt molecular clades represent cryptic morphospecies, we identified three anatomical areas most likely to differ in cases of recent speciation: external morphology, the chitinous feeding structures (radulae and jaws) and the reproductive system.…”
Section: Resultsmentioning
confidence: 99%
“…Observations of nudibranch and snail predation on pelagic coelenterates are largely concerned with predation on the neuston (Lalli & Gilmer, 1989). The glaucid nudibranchs, such as Glaucus atlanticus Forster, 1777 and Glaucilla marginata Bergh, 1868, are predators of the chondrophores Velella and Porpita and the siphonophore Physalia (Thompson & Bennett, 1970). As with the benthic nudibranchs they are able to utilize the prey nematocysts, particularly from Physalia, and concentrate them in cnidosacs for defence (Thompson & Bennett, 1969;Bebbington, 1986).…”
Section: Cnidaria and Ctenophoramentioning
confidence: 99%
“…More recent work (Graham, 1938;Edmunds, 1966;Thompson & Bennett, 1970;Harris, 1971;Mariscal, 1974;Conklin & Mariscal, 1977;Day & Harris, 1978) has shown that nudibranchs are able to absorb certain kinds of nematocyst selectively from their cnidarian prey and subsequently use them for their own defence. A particularly graphic example of this phenomenon was given by Thompson & Bennett (1970) who correlated the fact that bathers in New South Wales were quite severely stung by pelagic nudibranchs with the presence in these creatures of Physalia defensive nematocysts. The mechanism by which nudibranchs are able to ingest and store selected nematocysts in their cnidosacs without eliciting discharge has not been studied in detail.…”
Section: Associations With Cnidariansmentioning
confidence: 99%